A facile approach for the synthesis of novel 1-oxa- and 1-aza-flavonyl-4-methyl-1H-benzo[d][1, 3]oxazin-2(4H)-ones by microwave enhanced Suzuki–Miyaura coupling using bidentate chromen-4-one-based Pd(ii)–diimine complex as catalyst1. Issue 94 (14th October 2015) - Kumar, Sumit; Ahmed, Naseem
<x xml:space="preserve">Abstract</x> A facile access to novel 1-oxa- and 1-aza-flavonyl-4-methyl-1H-benzo[d][1, 3]oxazin-2(4H)-ones using microwave assisted Suzuki coupling of bromo flavones with boronic acids using a novel catalytic system (C) under aerobic condition is reported.